Analisis Perbandingan Metode Goodwil dan Metode Bonus dalam Perlakuan Akuntansi Perubahan Pemilikan Persekutuan - Faudhillah Kirana Putri; Nur Anita Chandra Putri; Fareliana Hardiyanti; Dara Ayu Melinda; Devina Nur Azizah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Changes in partnership ownership, such as the entry of new partners or changes in ownership proportions, have significant accounting implications for capital recognition and financial statement presentation. Two commonly used methods for recording these changes are the goodwill method and the bonus method. This article aims to analyze and compare the accounting treatment of the goodwill and bonus methods for changes in partnership ownership and to assess the appropriateness of their application based on business characteristics and financial reporting objectives. The research method used is a qualitative approach using literature review techniques, including accounting textbooks, financial accounting standards (PSAK and IFRS), and relevant scientific journals. The analysis results indicate that the goodwill method is able to more realistically represent the partnership's economic value through the recognition of intangible assets, but it carries a higher level of complexity and subjectivity. Conversely, the bonus method offers simplicity in recording and stability in financial statements, but is less likely to reflect the partnership's overall market value. Therefore, the choice of accounting method must consider the scale of the partnership, the complexity of the transactions, and the need for transparency and relevance of financial information.